Water and wastewater management for sustainable viticulture and oenology in South Portugal – a review - Costa, Joaquim (2020)
Assessing sustainability of the wine industry requires improved characterization of its environmental impacts, namely in terms of water use. Therefore, quantification of water inputs and wastewater (WW) outputs is needed to highlight inefficiencies in wine production and related consequences for the environment. Water use and WW generation in irrigated viticulture and oenology remains insufficiently quantified for dry Mediterranean regions (e.g. South Portugal). This paper is focused on wine production under warm and dry climate conditions in the winegrowing region of Alentejo (South Portugal). This region experiences increasingly dry conditions, while the irrigated area keeps expanding, which puts exacerbates the pressure on existing local and regional water resources. Additionally, more erratic variation in climate conditions and the tendency for increasingly extreme climate events (e.g. heat waves) pose more challenges to Alentejo’s wine sector. We conclude that quantitative information on water use and management is not always easy to obtain or access, which hinders improved strategies and/or policies for water use at farm, winery and region-level. Up-to-date statistics and robust metrics can help to better characterize water use and WW flows for Alentejo’s wine region, while optimizing management in vineyards and wineries, in companies and region-wide. The paper is focused on a “Farm-Winery” scenario, which is the most common in South Portugal’s wine sector